Luminescence and energy transfer studies of Ce3+/Dy3+ doped fluorophosphate glasses - Rao, V. Rajeswara; Devi, L. Lakshmi; Jayasankar, C. K.; Pecharapa, Wisanu; Kaewkhao, J.; Depuru, Shobha Rani (My University, 2019)
The fluorophosphate (PKABfNf:P2O5+K2O+Al2O3+BaF2+NaF2) glasses doped with single and co-doped (Ce and/or Dy) were prepared by conventional melt quenching technique and characterized their luminescence properties. The emission spectra of co-doped glass (PKABfNfCeDy) showed a broad blue band of Ce3+ ions combined with the sharp peaks of Dy3+ ions. Judd-Ofelt (JO) intensity parameters have been obtained from the optical absorption spectra of 1.0 mol% of Dy3+ (PKABfNfDy1.0) glass. JO theory has been used to find the radiative properties of PKABfNfDy1.0 glass by using Futchbauer-Ladenbergh formula. The (Ce3+/Dy3+) co-doped glass exhibit radiative energy transfer (ET) from Ce3+ to Dy3+ upon UV excitation and then intensity is increased with increase in Dy3+ ion concentration. The ET mechanism from Ce3+ to Dy3+ ion has been analyzed. The theoretical ET efficiency and quantum yield values were calculated from the emission spectrum of the Ce3+ and (Ce3+/Dy3+) co-doped glasses. These results suggest that the co-doped PKABfNfCeDy glasses are promising candidate for commercial white light applications.
Keywords: Cerium; Dysprosium; Energy transfer; Fluorophosphate glasses; Judd-Ofelt analysis; Quantum yield; W-LEDs